Perancangan Sistim Monitoring Parkir Mobil Berbasis Web - Muhammad Irmansyah; Efrizon Efrizon; Era Madona; Roni Putra (Teknik Elektro Politeknik Negeri Padang, 2018)
This research is an information technology innovation for long distance monitoring system in realtime through WEB which applied to car parking system. This intelligent parking system is designed to solve the problems of parking car in Politeknik Negeri Padang. In this system, the driver gets information trough the web about the empty and the filled area in the parking. This system is an automated system using infrared and photodiode as sensor to identify the existences of the car in parking area and controlled by microcontroller. WEB to monitoring and inform the condition of slot parking area to the car driver using smartphone and can be accessed from everywhere at the web address ee.polinpdg.ac.id/parkir. Computer server is a WEB server and database server to save the program and monitoring data result.